The Hybrid Specialization Model: Navigating Bureaucratic Rigidity through GovTech Co-creation in Indonesia - Ajeng Amalia Andi; Dodie Tricahyono; Agus Salim Andi (Pt. Anagata Sembagi Education, 2026)
This study investigates how GovTech firms navigate bureaucratic rigidity to accelerate digital maturity in Indonesian local government. It examines the evolution of client needs, the operationalization of collaborative governance, and the structural design of a